Assessment of Risk Factors Related to Environmental Factors and Herd Management for Bovine Respiratory Syncytial Virus and Bovine Parainfluenza Virus‐3 Infections Frequently Observed in Beef and Dairy Cattle - Ali Küçük; Yakup Yildirim; Bekir Çetintav (Veterinary Medicine and Science)
ABSTRACT Background Bovine Respiratory Disease Complex (BRDC) represents a multifactorial infection that poses a significant threat to animal health, leading to severe and fatal pneumonia outbreaks in large herds. Objective In this study, the molecular diagnosis of Bovine Parainfluenza Virus Type 3 (BPIV3) and Bovine Respiratory Syncytial Virus (BRSV) was targeted in nasal swab samples collected from cattle with clinical signs of respiratory infections. Furthermore, this study aimed to identify possible environmental and herd management‐related risk factors associated with the occurrence of these infections in herds/farms where BPIV3 and BRSV were detected, using statistical methods. Methods Therefore, a total of 200 nasal swab samples were randomly collected from 24 different cattle herds with respiratory infection outbreaks, representing 10% of each herd population. Results In the study, which utilized the RT‐PCR technique, viral nucleic acid of BPIV3 was detected in 8% (16/200) of the samples, and BRSV was detected in 11.5% (23/200) of the samples. In addition, logistic regression models incorporating both fixed and multiple variables identified the following risk factors for BRSV infection: in the univariate regression analysis, quarantine status, air quality, the period of disease occurrence and previous occurrence of BRDC in the farm; and in the multivariate analysis, the disease period, herd size, bedding type and qualitative air quality were significant risk factors for the presence of infection in the sampled herds. For BPIV3, univariate regression analysis indicated that animal transport, housing type, ventilation and the duration from infection onset to sampling were risk factors, while in multivariate analysis, age, duration from infection onset to sampling, and air quality were identified as risk factors for infection in the sampled herds. Conclusion A statistical relationship was demonstrated between BRSV and BPIV3 infections in cattle and certain herd, environmental and infection‐related factors, identifying these factors as risk factors contributing to the occurrence of these infections.